2023
DOI: 10.1037/apl0001017
|View full text |Cite
|
Sign up to set email alerts
|

Asians don't ask? Relational concerns, negotiation propensity, and starting salaries.

Abstract: In the U.S., Asians are commonly viewed as the “model minority” because of their economic prosperity. We challenge this rosy view by revealing that certain Asian groups may be susceptible to lower starting salaries. In Study 1, we analyzed 19 class years of MBAs who accepted full-time job offers in the U.S. At first glance, Asians appeared to have starting salaries similarly high as Whites’. However, a striking gap emerged once we distinguished between East Asians (e.g., ethnic Chinese), Southeast Asians (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…Second, we extend the literature on the Bamboo Ceiling (9,37,41,52). While previous studies focused on EAs' underrepresentation in leadership (9,41), the current studies revealed EAs' underperformance in the classroom.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Second, we extend the literature on the Bamboo Ceiling (9,37,41,52). While previous studies focused on EAs' underrepresentation in leadership (9,41), the current studies revealed EAs' underperformance in the classroom.…”
Section: Discussionsupporting
confidence: 57%
“…Third, we contribute to the literature on cultural psychology by elucidating the role of cultural background in academic performance in professional schools. Moreover, we move beyond the East-West contrast to expose differences within the "Asian" umbrella (9,41,52,55). In light of the current findings, future studies should distinguish between EAs and SAs both theoretically and empirically (e.g., when collecting demographic information and conducting analyses).…”
Section: Discussionmentioning
confidence: 89%
“…This increasingly influential framework differentiates between three types of cultures: dignity, face, and honor cultures (Aslani et al, 2013(Aslani et al, , 2016Leung & Cohen, 2011;Lu, 2023;Yao et al, 2017). The framework posits that while dignity cultures correspond to individualistic cultures like the United States, face and honor cultures represent two distinctive forms of collectivistic culture (Y.-H. Kim & Cohen, 2010;Leung & Cohen, 2011;Yao et al, 2017).…”
Section: Why East Asians Are Stereotyped As Less Creativementioning
confidence: 99%
“…By contrast, heavily impacted by Confucianism, face cultures (e.g., EA cultures) emphasize conformity, humility, and acceptance (Leung & Cohen, 2011;Lu, 2023). These cultural values are reflected by EA proverbs "The boughs that bear most hang lowest" and "The nail that sticks out gets hammered down"-in clear contrast to the American proverb "Don't hide your light under a bushel" (H. Kim & Markus, 1999;Markus & Kitayama, 1991).…”
Section: Why East Asians Are Stereotyped As Less Creativementioning
confidence: 99%
“…Thus, we also contribute to research by spotlighting Asian workers' experiences of incivility during the pandemic, where heightened xenophobia against this group has been documented (e.g., Dhanani & Franz, 2020; Nguyen et al, 2022) and calls have been raised to understand its causes in order to develop interventions to protect this group (e.g., Sinclair et al, 2020). Additionally, there is a tendency in the literature to treat all Asians as a monolithic or homogenous group, ignoring within‐group differences (e.g., Lu, 2022; Lu et al, 2020). However, research has shown that the invalidation of interethnic differences is a frequent microaggression experienced by Asian individuals that negatively affects their health and well‐being (Ong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%